Cancellous Bone Versus Tricalcium Phospate (TCP) For Bone Grafting: A Literature Review And Case Report Of Alveolar Bone Grafting In Cipto Mangunkusumo Hospital - Maulana, Muhammad Iqbal; Primadian, Akmal; Pancawati, Julieta; Bangun, Kristaninta (Lingkar Studi Bedah Plastik Foundation, 2017)
Background: In the last decade, there are various methods of bone grafting in plastic surgery. Cancellous bone is more often used as bone graft than cortical bone due to its high osteoconductivity and osteogenic capability. The synthetic materials for bone graft such as tricalcium phospate (TCP) and hydroxy-apatite can be use as new alternative for bone grafting surgery. Methods: The PubMed® databases were searched using the terms: ‘bone graft OR bone grafting’ AND ‘cancellous bone OR iliac crest OR tibia’ AND ‘tricalcium phospate OR tricalciumphospate OR tri calcium phospate’, restricted to English language, and to a publication period from January 2010 to January 2017. The inclusion criteria were any kind of research paper that compared the utility of TCP synthetic graft and autograft as a bone graft. Results: Out of 139 selected studies, only 8 met the inclusion criteria. In 6 publications TCP graft has similar outcome and in 1 publication have a better result in reducing post operative complication. Conclusion: TCP graft can be used as substitution for autograft in particular clinical conditions and surgical methods.